1983
DOI: 10.1111/j.1151-2916.1983.tb10029.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot‐Pressing Temperature on the Thermal Diffusivity/Conductivity of SiC/AlN Composites

Abstract: Data are presented for the thermal diffusivitylconductivity of hot-pressed mixtures of S i c and AIN. Results indicate that hot-pressing at higher temperatures, which permits solid-solution formation, results in significantly lower thermal diflusivityl conductivity than is obtained by hot-pressing at lower temperatures, at which discrete phases exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The thermal conductivity of SiC-AlN ceramics hot-pressed at lower temperatures (1850-2000 • C) was significantly higher than that of the samples prepared at higher temperatures (2100 • C or 2200 • C), indicating that 2H ss formation did not increase the thermal conductivity of the ceramics [30]. The thermal conductivities of the SiC-AlN ceramics prepared at 1850-2000 • C ranged from 30 to 50 W/m K, depending on the AlN content, whereas the thermal conductivity of ceramics hot-pressed at 2100 • C or 2200 • C ranged from 15 to 35 W/m K at RT [30,31]. A maximal value of 73 W/m K was obtained for the SiC-25 wt% AlN ceramics when the sintering temperature was lower than 2150 • C [29].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…The thermal conductivity of SiC-AlN ceramics hot-pressed at lower temperatures (1850-2000 • C) was significantly higher than that of the samples prepared at higher temperatures (2100 • C or 2200 • C), indicating that 2H ss formation did not increase the thermal conductivity of the ceramics [30]. The thermal conductivities of the SiC-AlN ceramics prepared at 1850-2000 • C ranged from 30 to 50 W/m K, depending on the AlN content, whereas the thermal conductivity of ceramics hot-pressed at 2100 • C or 2200 • C ranged from 15 to 35 W/m K at RT [30,31]. A maximal value of 73 W/m K was obtained for the SiC-25 wt% AlN ceramics when the sintering temperature was lower than 2150 • C [29].…”
Section: Introductionmentioning
confidence: 52%
“…The corrected value (κ c ) [42] of the thermal conductivity in the SAN0 specimen (using the same relative density (99.9%) as those of the SiC-AlN ceramics) was 121.2 W/m K. Thus, the addition of AlN to SiC led to a reduction in thermal conductivity. The thermal conductivity of the 2H ss phase was in the range of 15-35 W/m K at RT [31] and the thermal conductivity of the SiC-AlN ceramics was in the range of 30-50 W/m K, depending on the AlN content [30]. Thus, as shown in Fig.…”
Section: Samplementioning
confidence: 97%
“…Vickers microhardness values were measured under a load of 4.9 N. Thermal diffusivity and heat capacity were measured by a laser-flash method. 20,21 Both circular surfaces of the specimen were coated with specified graphite spray to avoid the transmission of laser beam through the specimen. Thermal conductivity was calculated from the product of thermal diffusivity, density, and heat capacity.…”
Section: (3) Analysis and Property Measurementmentioning
confidence: 99%
“…(A) Thermal Conductivity: Solid-solution formation caused a drastic decrease in thermal conductivity and diffusivity in the SiC-AlN system. 6,21 The thermal conductivity for a fixed nominal composition changed as an approximate indication of the extent of solid-solution formation. Bensten et al 21 reported that hot pressing at higher temperatures, which permitted solid-solution formation, resulted in significantly lower thermal conductivity than that obtained by hot pressing at lower temperatures, at which discrete phases existed.…”
Section: (2) Dependence Of Thermal and Mechanical Properties On The Smentioning
confidence: 99%
See 1 more Smart Citation